Volumetric analysis of root canals obturated with cold lateral condensation, single-cone and thermoplasticized gutta-percha techniques using spiral computed tomography: An in vitro study - Shanol Anusha Crasta; Jyothi Kashi Nanjundasetty; Venugopal Panuganti; Jayashankara Chatra Marigowda; Sharath Kumar; Anil Kumar (Wolters Kluwer Medknow Publications, 2014)
Aim: To evaluate and compare the volume percentage of root canals obturated with gutta percha (POV), with various techniques using spiral computed tomography (SCT). Materials and Methods: Forty-five mandibular first premolar teeth were instrumented using Race files and randomly divided into three groups of 15 teeth each (n = 15). The volume of root canal space was measured using SCT and the root canals were obturated as follows: Group 1-lateral condensation, Group 2-single-cone obturation and Group 3-thermoplasticized gutta-percha technique. The filled volume of root canals was measured using SCT and POV was calculated in total and at apical, middle and coronal third individually. The data was statistically analyzed using one-way ANOVA and Tukeys post hoc multiple comparison tests. Results: An intergroup comparison of the mean value of POV showed a statistically significant difference ( P < 0.05) in the middle third and in total when group 1 was compared to group 2. Conclusion: All the groups showed 100% POV at the apical third. Group 2 showed least POV at the middle third of the root canal.